PENGETAHUAN IBU HAMIL TENTANG SENAM HAMIL DI DESA MUARA RUMBAI KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Wahyuny, Romy (Jurnal Martenity and Neonatal, 2019)
Pregnancy gymnastics is a fitness program that is intended for pregnant women. As for the purpose of prenatal pregnancy exercise is physiological (natural) delivery with mothers of healthy babies, mental and physical preparation for pregnant women, good, rhythmic and strong contractions in the lower uterine segment, cervix, pelvic floor muscles, relaxaxasia, health information (including hygiene) about pregnancy to pregnant women, husband / family or the community. In simple pregnancy pregnant women will be useful, among others, reduce or relieve lethargy, difficulty sleeping, discomfort, stress. This research is a descriptive and cross sectional design. The population in this study were all pregnant women in the village of Muara Rumbai as many as 60 people, and the number of 46 samples, in this study the measuring instrument used was a question of 15 items. The type of data used in this study is primary data. The results of research on the knowledge of pregnant women about pregnancy exercises with good knowledge are 1 respondent (2.2%), sufficient knowledge is 30 respondents (65.2%), and those who lack knowledge are 15 respondents (32.6%). From the results of the study it can be concluded that the knowledge of pregnant women about pregnancy exercise is sufficient 30 respondents (65.2%). It is recommended to pregnant women to increase knowledge about pregnancy exercises so that it can reduce sleep discomfort and stress.